Determinants of Digital Zakat Adoption among Generation Z in Indonesia - Abdul Malik; Jasri; Harun Alrasyid; Siti Walida Mustamin (Journal of Contemporary Applied Islamic Philanthropy, 2026)
Purpose: This study aims to examine the determinants of digital zakat adoption among Generation Z within the framework of Islamic philanthropy. Methodology: This study employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on data collected from 130 respondents in Makassar, Indonesia. Findings: The findings demonstrate that trust is the most dominant factor influencing digital zakat adoption, followed by technology use and financial inclusion, while financial literacy shows the weakest effect. The results indicate that trust exhibits the strongest influence, suggesting its central role in shaping digital zakat behavior. The study uncovers a behavioral paradox in which trust and technological convenience play a more significant role than financial literacy. These findings emphasize the importance of developing trust-based digital ecosystems to enhance participation in Islamic philanthropic practices. This study introduces a behavioral paradox in digital zakat adoption, showing that trust and technological convenience play a more dominant role than financial literacy in influencing Generation Z’s digital zakat behavior. This finding offers a new perspective within the discourse of Islamic philanthropic behavior in the digital era. The findings also provide practical implications for zakat institutions in designing transparent, secure, and user-friendly digital ecosystems to strengthen public participation in digital zakat practices.